12‐Month outcomes of transcatheter tricuspid valve repair with the PASCAL system for severe tricuspid regurgitation. Issue 6 (4th March 2021) - Kitamura, Mitsunobu; Fam, Neil P.; Braun, Daniel; Ruf, Tobias; Sugiura, Atsushi; Narang, Akhil; Connelly, Kim A.; Ho, Edwin; Nabauer, Michael; Hausleiter, Jörg; Weber, Marcel; Nickenig, Georg; et al.
Abstract: Objectives: We investigated the durability of tricuspid regurgitation (TR) reduction and the clinical outcomes through 12 months after transcatheter tricuspid valve repair (TTVr) with the PASCAL Transcatheter Valve Repair System. Background: TTVr has rapidly developed and demonstrated favorable acute outcomes, but longer follow‐up data are needed. Methods: Overall, 30 patients (age 77 ± 6 years; 57% female) received PASCAL implantation from September 2017 to May 2019 and completed a clinical follow‐up at 12 months. Results: The TR etiology was functional in 25 patients (83%), degenerative in three (10%), and mixed in two (7%). All patients had TR severe or greater (massive or torrential in 80%) and heart failure symptoms (90% in NYHA III or IV) under optimal medical treatment. Single‐leaflet device attachment occurred in two patients. Moderate or less TR was achieved in 23/28 patients (82%) at 30 days, which was sustained at 12 months (86%). Two patients underwent repeat TTVr due to residual torrential TR (day 173) and recurrence of severe TR (day 280), respectively. One‐year survival rate was 93%; 6 patients required rehospitalization due to acute heart failure. NYHA functional class I or II was achieved in 90% and 6‐minute walk distance improved from 275 ± 122 m at baseline to 347 ± 112 m at 12‐month (+72 ± 82 m, p  < .01). There was no stroke, endocarditis, or device embolization during the follow‐up. Conclusions: Twelve‐month outcomes from this multicenter compassionate use experience with the PASCAL System demonstrated high procedural success, acceptable safety, and significant clinical improvement.